Perbedaan Angka Kejadian Diare Balita Pada Kelompok Masyarakat Yang Sudah Memiliki Jamban Keluarga Dengan Kelompok Masyarakat Yang Belum Memiliki Jamban Keluarga - Anggitasari, Januariska Dwi Yanottama; , Prof. Dr. Bambang Soebagyo, dr. Sp.A (K); , dr. Yusuf Alam Romadhon, M.Kes (2015)
Background: Diarrhea is a major cause of morbidity and mortality in infants. The low number of healthy family toilet is a risk of causing diarrhea. Objective: To determine the difference of diarrhea incident among children under five years in the community who have family toilet with community who do not have family toilet. Methods: This study is an analytical observational research using cross-sectional approach in public health service working area of Grogol Sukoharjo with 60 samples. Family toilet ownership data and diarrhea incidence datagot from questionnaire. Analytic statistic used Chi-Square test. Results: The proportion of children who had diarrhea in the community who have family toilet is 10 and in the community who do not have family toilet is 18. Based on Chi-Square analytical statistic is obtained X2 value = 4,286 and p value = 0,038 (p<0,05) that means there is a difference of diarrhea incident among children under five years in the community who have family toilet with community who do not have family toilet. Conclusion: There is a difference of diarrhea incident among children under five years in the community who have family toilet with community who do not have family toilet.